Corporate governance and Real Activities Manipulation (Real Earnings Management) (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2014)
This paper is performed based on the relation between corporate governance on Iranian corporations' performance 2006-2012 financial years. The aim of this study is to determine the relationship between the elements of firm sovereignty and the management of real profit in the realm of the study. The methodology of the study is based on the drawing a conclusion and the gathering of descriptive data and also based on practical application aim. The descriptive method is from correlated type and multi variable regressions are used to analyze the data and to examine assumption. Considering the first basic assumption (among firm sovereignty (concentration of ownership) and second assumption (between firm sovereignty (independence of the board of directors) and handling real activities there is a relation. The obtained conclusions show that: based on the first assumption there is a negative and meaningful relation between independency of board of directors and management of real profit based on unusual expenses of production. However no meaningful relationship was observed between concentration of property and real earning management. Based on the second assumption: there is a negative and meaningful relationship between the independency of the board of directors and the real management of real profit based on arbitrary expenses, however when the previous models is based on management of real profit model and arbitrary expenses and is considered, no meaningful relationship was observed between concentration of the property and possession and real earning management.